Applying a Self-Regulation and Communication Framework to Autism Intervention - A. Binns (Moscow State University of Psychology and Education, 2019)
Accumulating evidence demonstrates the important role of self-regulation in children's academic success and development of social and emotional wellbeing. Binns, Hutchinson and Oram Cardy proposed a framework designed to help clinicians to understand the impact that stress can have on children's ability to attain a state of regulation and engage with their environment and, simultaneously, to support children's communication and self-regulation capacities. In this article, I review challenges in the domain of self-regulation specific to children with autism and share special considerations for applying our framework to autism intervention.